Advertisement Remove all ads

In the Given Figure, Prove That: (I) ∆ Acb ≅ ∆ Ecd (Ii) Ab = Ed - Mathematics

Sum

In the given figure, prove that:
(i) ∆ ACB ≅ ∆ ECD
(ii) AB = ED

Advertisement Remove all ads

Solution

(i) In Δ ACB and Δ ECD,

AC = CE ................(given)

∠ACB = ∠DCE ............(vertically opposite angles)

BC = CD .............(given)

∴ Δ ACB ≅ Δ ECD ..............(S.A.S. Axiom)

(ii) Hence AB = ED ................(c.p.c.t.)

Hence proved.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 7 ICSE
Chapter 19 Congruency: Congruent Triangles
Exercise 19 | Q 5
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×